Changes of public environmental awareness in response to the Taihu blue-green algae bloom incident in China - Xu, L.; Shen, J.; Marinova, Dora; Guo, Xiumei; Sun, F.; Zhu, F. (Springer Science+Business Media B.V. (Kluwer Academic Publishers), 2013)
Environmental problems are becoming increasingly severe in China with industrial discharges and household sewages being the main sources of water pollution in the country. For example, in the case of Taihu Lake, more than half of the total phosphorus in the lake comes from household sewage. While industrial pollution can be treated through technology innovation and controlled by environmental regulations and laws, decreasing household sewage relies entirely on residents. Raising public environmental awareness therefore is essential for ensuring effective environmental improvement and protection. A quantitative assessment of public awareness can inform policy and decision makers; however, not many such studies have been conducted. Changes in the awareness levels in response to a major environmental pollution incident are of particular interest because of the people’s first-hand experience of the triggered consequences. The present paper establishes a system of indicators for the assessment of public environmental awareness. Combined with a fuzzy matter-element analysis method, a model is set-up to quantitatively assess the public environmental awareness. The model is then applied to assess the environmental awareness of the residents of Wuxi City after its major lake Taihu suffered a severe algae bloom in 2007. This study examines whether this serious environmental incident affected people’s environmental awareness and to what degree. The findings show that the matter-element model is capable to resolve well the fuzziness of the ranking affiliation and classification of subjective perceptions, such as public environmental awareness. They show that this environmental incident has had significant positive impacts on the environmental awareness of Wuxi residents. The paper concludes with recommendations related to raising public environmental awareness.